Optimization Research on the Construction of Rural Teacher Teams under the Background of Rural Revitalization Strategy: An Analysis Based on the ERG Theory Perspective - Yan, Guidan; Ye, Fabao (Journal of Educational Research and Policies, 2025)
This research examines the current state and challenges of building a team of rural teachers within the framework of the rural revitalization strategy, utilizing ERG theory to explore three key aspects: survival, relationships, and growth. The findings indicate that rural teachers face numerous issues related to their survival security, social connections, and professional development, which hinder both stability and the quality of education. The study proposes strategies such as raising salaries, reducing burdens, and strengthening home-school cooperation to enhance teachers’ job satisfaction, social integration, and professional development, and to promote rural revitalization and education modernization.